Superstitious Ritual Behavior in Sports: A Comparative Study among Various Athletes - Mukherjee, Ashoke; Shaikh, Abdul Sarjen (Journal of Sports Research, 2022)
The aim of the study was to assess the superstitious ritual behavior of the University level sports persons and to find out that male or female athlete who believes more in superstitions. Eighty-three (83) University level athletes (Male – 44 and Female – 39) of 18 to 25 years from Visva-Bharati University, Santiniketan, India have been selected through purposive random sampling. The Superstitious Ritual Questionnaire (SRQ) framed by Flanagan (2013) has been used to assess the superstitious ritual behavior and its effectiveness on sports performance enhancement. In overall percentage 25.30% of male athletes and 20.48% of female athletes are of the opinion that sometimes superstitious ritual behavior is effective in sports performance enhancement. Statistical analysis does not reveal any significant relationship between superstitious ritual behavior (Male: Mean 108.48, SD 22.38; Female: Mean 109.03, SD 24.46) and its effectiveness (Male: Mean 3.23, SD 0.74; Female: Mean 2.80, SD 0.73) in sports performance enhancement for both male (r = 0.263) and female (r = 0.140) group. As per as the opinion towards the effectiveness of superstitious rituals behavior on sports performance enhancement is concerned the male athletes found to be significantly more superstitious than female athletes (t = 2.69). So it can be concluded that irrespective of male or female mostly all the athletes believes in some sort of superstitious rituals may be to control luck and fear of failure, increase confidence, maintain focus, decreases stress and anxiety etc. at the highest level of sports competitions.